Effects of Moringa oleifera leaf meal on performance and carcass yield of broilers - Gabriel Miranda Macambira; Carlos Bôa-Viagem Rabello; Manuel Isidoro Valdivie Navarro; Cláudia da Costa Lopes; Elainy Cristina Lopes; Guilherme Rodrigues do Nascimento; Helia Sharlane de Holanda Oliveira; Jaqueline de Cássia Ramos da Silva (Revista Brasileira de Zootecnia, 2022)
ABSTRACT This study evaluated the effects of including Moringa oleifera (moringa) leaf meal on performance, carcass yield and characteristics, and relative organ weights of broilers from 10 to 42 days of age. We distributed 420 male Cobb 500 chicks in a completely randomized design with five treatments and six replicates with 14 birds each. Treatments consisted of five experimental diets in which the moringa leaf meal was included at 0, 1.5, 3.0, 4.5, and 6.0% in the diets. The following performance variables were evaluated: weight gain, feed intake, and feed conversion; weights and yields of carcass, carcass traits, organs, and abdominal fat; and feet color. Significant differences between the treatment means were analyzed by Dunnett’s test. The meal inclusion levels did not affect performance, carcass characteristics and yield, or organs weight. However, feet pigmentation increased linearly, and abdominal fat was greater only at the 1.5% level when compared with the control group. Moringa leaf meal can be included in the diet of broilers from 10 to 42 days of age, up to the level of 6%, without compromising performance or carcass yield of these birds.